Yatiris en el siglo XXI. El conocimiento, la política y la nueva generación - Anders Burman (Centre de Recherches sur les Mondes Américains, 2011)
Indigenous rituals escorted Evo Morales throughout his first years as president of Bolivia. The art and the ritual practices of the yatiri, the Aymara healer and ritual specialist, are going through interesting transformations entering new political spaces of power. But which role does this therapeutic knowledge and ritual practice actually play in the present political process and how should this be understood? In this ethnographic paper I explore the interlacing of political/governmental and ritual/healing practices, and the alternative readings of the political and cultural dynamics of contemporary Bolivian society offered by the yatiris. Central to these readings are the correspondences between colonialism and illness, and between decolonization and healing.